Dampak Relokasi Pedagang Kaki Lima Di Kabupaten Tulungagung - , Gading Gamaputra; , Dr. Agus Heruanto Hadna M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Street vendor relocation policy done by Tulungagung regency was based on Regulation of Tulungagung regent no 2/2005 on relocation of street vendor in the town square and its vicinity. The policy caused street vendors were relocated from Tulungagung square to Pujasera area. Based on Satpol-PP data, there were 238 street vendors relocated to Pujasera area. However, currently there were only 51 street vendors in the Pujasera area. This research was intended to describe policy of street vendor relocation to Pujasera as means to govern street vendor and economic impact of the relocation. It used descriptive method to discover the past and current problems. Qualitative data was intended to explore behavior, perception, motivation and action in holistic manner. Data was collected with observation and interview where respondents were determined elitist with snowball sampling. Impact analysis was done by comparing before and after relocation. The study was conducted after the relocation to the Food Court to the image. First, economic activities run more flexible where free traders to trade 24 hours. Second, traders have a place and do not need to dismantle the tent pairs trading. Third, hawkers capital obtained from private capital, conventional loans, and the failure of financial aid from the government. Fourth, place of business hawkers away in the suburbs that resulted in access and all efforts to attract customers are not able to increase revenues street vendors. Fifth, There was a decrease in the amount of income after relocation of street vendors The study recommends. First, the government and street traders sit together to discuss the appropriate steps to attract and gain customers as efforts to increase revenue hawkers. Second, increase access to capital in the financial institutions sector. Third, the provision of business management guidance to vendors who can mobilize capital management and entrepreneurial mentoring and the creation of partnerships with government with the merchant, merchant to merchant and the merchant community..